Global or strategic trade?: some observations on President Donald Trump’s style of making domestic and foreign policy (Ius Novum, 2019)
The article refers to the main theses of the author’s fourth edition of Handel międzynarodowy published by C.H. Beck. It is a handbook that, due to its didactic nature, only updates information about the regulations of global and regional international trade. The preparation of this article for publication results from the reflections of a commentator who observes the transformation of the United States’ priorities during Donald Trump’s presidency. An observer of trade policy must consider whether we deal with a “new era” in international trade. The answer to this question, whether positive or not, is subject to agreement. Nevertheless, the inclination of President Trump, a helmsman of the policy of the most important partner in international trade, to trivialise “trade wars” and emphasise that the US interests are of crucial importance is unquestionable and justifies asking successive detailed questions: To what extent does strategic trade, carried out from the perspective of one country’s benefits, substitutes for global trade? Is President Trump first of all a businessman or a political strategist? Is the possibility of impeachment or even bringing criminal charges against the president who is in office, which is discussed by American law experts, realistic or is it part of the nature of the United States’ political scene? What are the prospects for re-election of the president, whose personal counsel, Michael Cohen, has been sentenced to three years’ imprisonment and a number of other associates are waiting for the results of an investigation into the collaboration with Russia during the presidential electoral campaign?
Keywords: globalisation and regionalisation; internationalism; glocalisation; anti-globalism; strategic trade; protectionism and isolationism; impeachment; national economic emergency; electoral democracy and populist democracy; recession